Effect of Lethal Concentration of Commercial Gasoline on Caspian Roach (Rutilus caspicus) - Aliakbar Hedayati; Fatemeh Darabitabar; Toktam Bagheri; Mohammad Moradzadeh; Omid Jafari (Hamadan University of Medical Sciences, 2016)
In this study, the mortality effects of commercial gasoline at different tested concentrations were evaluated on the common roach (Rutilus caspicus) and LC50 values for each time period (24, 48, 72, and 96 hours) have been determined. Roach with an average weight of 3.1 ± 0.45 g and lengths of 4 ± 0.25 cm were used in this study. After transferring the 200 fish to the laboratory, they were kept in tanks of 100 liters for one week to adapt them to the experimental conditions. After the adaptation period, 100 fish were selected randomly and divided into 14 treatments (0, 2, 5, 10, 20, 40, 60, 80, 100, 200, 400, 600, 800, and 100 ppm commercial gasoline). The treatments were completed in triplicate. The results of this study show that the 96-hour LC50 of commercial gasoline is 600.2 ± 0.44 ppm and the maximum allowable concentration (MAC) is 60.02 mg/L. The study demonstrates the deadly effects of commercial gasoline on the Caspian roach. Spillage of diesel and gasoline fuels from transport tankers can enter rivers and eventually the marine ecosystem, and reach nursery and spawning areas where it can become a serious threat to fish survival.